5y-2(y-1)+6=x

Simple and best practice solution for 5y-2(y-1)+6=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-2(y-1)+6=x equation:


Simplifying
5y + -2(y + -1) + 6 = x

Reorder the terms:
5y + -2(-1 + y) + 6 = x
5y + (-1 * -2 + y * -2) + 6 = x
5y + (2 + -2y) + 6 = x

Reorder the terms:
2 + 6 + 5y + -2y = x

Combine like terms: 2 + 6 = 8
8 + 5y + -2y = x

Combine like terms: 5y + -2y = 3y
8 + 3y = x

Solving
8 + 3y = x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 3y = -8 + x

Combine like terms: 8 + -8 = 0
0 + 3y = -8 + x
3y = -8 + x

Divide each side by '3'.
y = -2.666666667 + 0.3333333333x

Simplifying
y = -2.666666667 + 0.3333333333x

See similar equations:

| 3x=15/8 | | 32-2x=6x | | 4/3v=24 | | -3(n-8)=-6n+27 | | 2n/3-4=12 | | 3x=2x-154 | | 19=2t^2-3t | | 5.12=4u | | 0.4x+3.9=5078 | | 2(4-3x)=4(2x+5) | | x/3=9.6 | | -5(-3p-7)=-13+3p | | -6(r+8)+11r=2(4-r)+8 | | 45=-15r | | 3x+7+2=32 | | x-109=105 | | (4-5i)(-2+7i)= | | y=(x)+1 | | x-0.2x=90 | | 25x^5/5x^2 | | (X+2)(y+4)=58 | | -14-r=8(r+5) | | Y=x*cos*x | | -10=a-19 | | A=-12+4 | | 4x+2y+8=58-xy | | 3(x-2)=75 | | 44=-15r | | -3x-17=x+3 | | 3x+26=x+12 | | 18.9=2.1xn | | 6x+19=49 |

Equations solver categories